The Statistical Characteristics of Atmospheric Ducts Observed Over Stations in Different Regions of American Mainland Based on High-Resolution GPS Radiosonde Soundings - Huang, Lang; Zhao, Xiaofeng; Liu, Yudi (Frontiers in Environmental Science, 2022)
The atmospheric duct is an anomalous atmospheric structure that affects the electromagnetic waves propagation. The important characteristics of the atmospheric ducts include duct probability, duct height, duct strength and thickness of the trapping layer. To investigate the statistical characteristics of atmospheric ducts over American mainland, four stations in different regions are chosen. The seasonal and diurnal variation of the characteristics of ducts is presented. The mechanism of the seasonal and variation of ducts are revealed and the relationship between the characteristics are researched. The duct strength correlates positively with the thickness of the trapping layer and the duct height correlates with them negatively. Besides, the duct relationship with the precipitation over different stations is clarified. It is found that the precipitation correlates positively with the probability of ducts caused by the vertical moisture gradient and the relation is negative when the ducts are caused by temperature inversion. This work is of great value to the statistical characteristics of atmospheric ducts over the America mainland.